New heterometallic Ir(iii)2–Eu(iii) complexes: white light emission from a single molecule. Issue 1 (8th August 2014) - Baschieri, Andrea; Muzzioli, Sara; Matteucci, Elia; Stagni, Stefano; Massi, Massimiliano; Sambri, Letizia
Abstract : Pure white light emission from a single-molecule Ir2 (iii )–Eu(iii ) complex can be achieved with appropriate ligands. Abstract : The design of a relatively simple bifunctional ligand led to the obtainment of three new Ir(iii )2 –Eu(iii ) heterometallic complexes. Variation of the degree of fluorination in the cyclometalating ligands coordinated to the Ir(iii ) centres allows tuning of the photophysical properties and pure white light emission from a single complex.